If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(5 + -5x) = 60 (5 * 4 + -5x * 4) = 60 (20 + -20x) = 60 Solving 20 + -20x = 60 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + -20x = 60 + -20 Combine like terms: 20 + -20 = 0 0 + -20x = 60 + -20 -20x = 60 + -20 Combine like terms: 60 + -20 = 40 -20x = 40 Divide each side by '-20'. x = -2 Simplifying x = -2
| 7x-3=6x-9 | | 16-32/4 | | .55*12+17= | | 7w-5=-6+2(w-7) | | 34-4b=18 | | 10-3v=49 | | 5-2d+4d-7+w= | | -2-3(1-x)=(-2x+7) | | 2m+(-3)=24 | | 5x-3+9x=4x-9 | | 2/3-1=20 | | 3n+19=28 | | -8h-64h=-2(7h+3)+2h | | -4x+7x-8=3(x-3)-5 | | 8m+28=24 | | 9+4.5= | | .15*12+35= | | 9(2m-3)-4(5+3m)=-3 | | 4d+6=8 | | 3-3k=5b | | A=-13+-2h | | -3+4r-3r=-5r+7r | | 30-23k=5b | | 6(x+6)+6=6x+2 | | X^2=4.5 | | 9x-9=8x+3 | | 2.75x+3y=.375 | | 10-x=2+3x | | 4(-1x+4)=-24 | | 1a-(-2h)=-13 | | 6h+3h=633 | | -12+2n=-7(-4-6n) |